2022
DOI: 10.1002/gch2.202100138
|View full text |Cite
|
Sign up to set email alerts
|

Developing Novel Biointerfaces: Using Chlorhexidine Surface Attachment as a Method for Creating Anti‐Fungal Surfaces

Abstract: There is an increasing focus in healthcare environments on combatting antimicrobial resistant infections. While bacterial infections are well reported, infections caused by fungi receive less attention, yet have a broad impact on society and can be deadly. Fungi are eukaryotes with considerable shared biology with humans, therefore limited technologies exist to combat fungal infections and hospital infrastructure is rarely designed for reducing microbial load. In this study, a novel antimicrobial surface (AMS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…We have previously demonstrated that it is possible to nitride metal surfaces and utilize the nitride layer as a functionalized surface to attach biocides. [ 28 ] Plasma nitriding of polymers is uncommon because it does not confer the same wear resistance properties seen in metals. The process normally requires extreme temperatures to modify steel surfaces.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously demonstrated that it is possible to nitride metal surfaces and utilize the nitride layer as a functionalized surface to attach biocides. [ 28 ] Plasma nitriding of polymers is uncommon because it does not confer the same wear resistance properties seen in metals. The process normally requires extreme temperatures to modify steel surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…[27] We have also shown that steel and air filters can be coated with the broad-spectrum biocidal agent chlorhexidine digluconate (CHDG) to develop antimicrobial surfaces that are efficacious against a range of pathogenic bacteria, fungi, and viruses. [28,29] Unlike previously developed biocide-coated technologies, this does not rely on biocide release for functional activity. In this study, we demonstrate the ability to extend this coating technology to plastic, creating surfaces that are highly effective against Gram-positive (S. aureus) and Gramnegative bacteria (E. coli), pathogenic fungi, and viruses, including SARS-CoV-2 as well as displaying durability against leaching.…”
Section: Introductionmentioning
confidence: 99%